Problems Regarding Treatment of Disturbed Land in Ukraine - Hunko, L.; Berezhna, K. (Land Management, Cadastre and Land Monitoring, 2021)
The article considers the problems and features of reclamation of disturbed lands of Ukraine in terms of regions, describes the need and importance of land protection in Ukraine and the world and the implementation of measures for reclamation of disturbed lands. The number of disturbed and reclaimed lands in Ukraine as of January 1, 2021 was analyzed and reclamation works were carried out for 2020. The main issues of legislative conflicts that arise during the reclamation of disturbed lands or "non-reclamation" are highlighted. The measures of state control over the use and protection of lands of all categories and forms of ownership conducted by the Main Departments of the State Geocadastre in the regions for the period 2017 - 2020 are analyzed. An example of the use of a spent limestone quarry for construction is given on the example of the Dalhalla Theater and why such foreign experience cannot be applied in Ukraine. The administrative responsibility for "failure" to rehabilitate disturbed lands is highlighted. The problem that arises when accepting already reclaimed lands by local governments or public authorities has been identified.Recommendations are given for the introduction of more effective measures for the restoration of disturbed lands.Key words: land reclamation, land protection, rational use, negative consequences, non-reclamation, measures, restoration, state control.